Pharmacological Targets of Kaempferol Within Inflammatory Pathways-A Hint Towards the Central Role of Tryptophan Metabolism - Stefanie Hofer; Simon Geisler; Rebecca Lisandrelli; Hieu Nguyen Ngoc; Markus Ganzera; Harald Schennach; Dietmar Fuchs; Julian E. Fuchs; Johanna M. Gostner; Katharina Kurz (MDPI AG, 2020)
The flavonoid kaempferol is almost ubiquitously contained in edible and medicinal plants and exerts a broad range of interesting pharmacological activities. Interactions with central inflammatory processes can be exploited to treat or attenuate symptoms of disorders associated with chronic immune activation during infections, malignancies, and neurodegenerative or cardiovascular disorders. Many drugs, phytochemicals, and nutritional components target the catabolism of the essential amino acid tryptophan by indoleamine 2,3-dioxygenase 1 (IDO-1) for immunomodulation. We studied the effects of kaempferol by in vitro models with human peripheral blood mononuclear cells (PBMC) and THP-1 derived human myelomonocytic cell lines. Kaempferol suppressed interferon-γ dependent immunometabolic pathways: Formation of the oxidative stress biomarker neopterin and catabolism of tryptophan were inhibited dose-dependently in stimulated cells. In-silico docking studies revealed a potential interaction of kaempferol with the catalytic domain of IDO-1. Kaempferol stimulated nuclear factor kappa B (NF-κB) signaling in lipopolysaccharide (LPS)-treated THP-1 cells, thereby increasing the mRNA expression of interleukin (IL) 1 beta, tumor necrosis factor, and nuclear factor kappa B subunit 1, while IL6 was downregulated. Data suggest that concerted effects of kaempferol on multiple immunologically relevant targets are responsible for its immunomodulatory activity. However, the immunosuppressive effects may be more relevant in a T-cell dominated context.